A1.19 Zinc and cadmium homeostasis is altered in rheumatoid arthritis synoviocytes. (31st January 2014) - Bonaventura, Paola; Lavocat, Fabien; Benedetti, Giulia; Lambroux, Aline; Albarede, Francis; Miossec, Pierre
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disease with uncontrolled proliferation of synoviocytes. Pro-inflammatory cytokines, notably IL-17 and TNF-α contribute to RA perpetuation. Zinc (Zn) is critical for the function of the immune system and its homeostasis is controlledby ZIPs importers, ZnTs exporters and Metallothioneins (MTs), metal binding proteins in cytosol. The aim of the work is the study of the homeostasis of Zn and other metals in RA compared to Osteoarthritis (OA) synoviocytes. Materials and Methods: A metal-enriched culture medium (Cadmium (Cd), Indium, Tin, Lead, Bismuth) was prepared with or without Zn (2ppm), IL-17 and TNF-α. Metal levels were studied by Induced-Coupled-Plasma Mass Spectrometry after a two week culture to estimate their Dissociation Constant cells/medium ((KD ) = (Me/Zn)cells/(Me/Zn)medium; Me: metal). mRNAs of Zn trafficking molecules were quantified by qRT-PCR in cells first treated overnight with or without IL-17 and TNF-α, then with addition or not of Zn (0.9 ppm) for 6 hours. Cd was added to inhibit Zn activity. Results: Metal quantification showed that Cd is preferentially absorbed by synoviocytes (OA, RA) compared to Zn (KD Cd/Zn = 100). IL-17 and TNF-α addition had a low effect on ZIP-8 but not on ZnT1 and MTs mRNA in both cells. Increasing Zn concentration (0.4, 0.9, 3.6 ppm) proportionally modified transporter expression and cytokines/Zn co-exposure enhanced their expression. MTs expression significantly increased with Cd exposure in comparison to the control situation (p < 0.01), which was further enhanced with cytokines. Controversially, addition of small amount (0.9 ppm) of Zn in the presence of Cd (0.1 ppm) reduced the Cd-induced MTs expression in both cell types. Importantly, the effects of Cd/Zn or cytokine addition were reduced in RA vs. OA synoviocytes resulting in a reduced apoptotic ratio of RA synoviocytes measured by Annexin V staining. Conclusion: Synoviocytes (OA, RA) preferentially absorb Cd, regardless to its toxicity. Homeostasis of Zn and Cd is modified in RA compared to OA synoviocytes. This could explain their resistance to apoptosis and their uncontrolled proliferation. Moreover addition of Zn could reduce Cd-induced apoptosis.